Acute sleep deprivation in mice generates protein pathology consistent with neurodegenerative diseases - Rowe, Rachel K.; Schulz, Philip; He, Ping; Mannino, Grant S.; Opp, Mark R.; Sierks, Michael R. (Frontiers in Neuroscience, 2024)
Insufficient or disturbed sleep is strongly associated with adverse health conditions, including various neurodegenerative disorders. While the relationship between sleep and neurodegenerative disease is likely bidirectional, sleep disturbances often predate the onset of other hallmark clinical symptoms.Neuronal waste clearance is significantly more efficient during sleep; thus, disturbed sleep may lead to the accumulation of neuronal proteins that underlie neurodegenerative diseases. Key pathological features of neurodegenerative diseases include an accumulation of misfolded or misprocessed variants of amyloid beta (Aβ), tau, alpha synuclein (α-syn), and TarDNA binding protein 43 (TDP-43). While the presence of fibrillar protein aggregates of these neuronal proteins are characteristic of neurodegenerative diseases, the presence of small soluble toxic oligomeric variants of these different proteins likely precedes the formation of the hallmark aggregates. We hypothesized that sleep deprivation would lead to accumulation of toxic oligomeric variants of Aβ, tau, α-syn, and TDP-43 in brain tissue of wild-type mice. Adult mice were subjected to 6 hours of sleep deprivation (zeitgeber 0-6) for 5 consecutive days or were left undisturbed as controls. Following sleep deprivation, brains were collected, and protein pathology was assessed in multiple brain regions using an immunostain panel of reagents selectively targeting neurodegenerative disease-related variants of Aβ, tau, α-syn, and TDP-43. Overall, sleep deprivation elevated levels of all protein variants in at least one of the brain regions of interest. The reagent PDTDP, targeting a TDP-43 variant present in Parkinson's disease, was elevated throughout the brain. The cortex, caudoputamen, and corpus callosum brain regions showed the highest accumulation of pathology following sleep deprivation. These data provide a direct mechanistic link between sleep deprivation, and the hallmark protein pathologies of neurodegenerative diseases, such as Alzheimer's and Parkinson's diseases.